Electroencephalography characteristics related to risk of sudden unexpected death in epilepsy in patients with Dravet syndrome - Kim, Jeong-Youn; Shin, Jeongyoon; Kim, Laehyun; Kim, Se Hee (Frontiers in Neurology, 2023)
Objective: To investigate the quantitative electroencephalography (EEG) features associated with a high risk of Sudden Unexpected Death in Epilepsy (SUDEP) in patients with Dravet syndrome (DS). Methods: Patients with DS and healthy controls (HCs) who underwent EEG were included in the study. EEG signals were recorded using a 21 channel digital EEG system, and pre-processed data were analyzed to identify quantitative EEG features associated with a high SUDEP risk. To assess the risk of SUDEP, SUDEP-7 scores were used. Results: A total of 64 patients with DS (38 males and 26 females, aged: 128.51 ± 75.50 months [range: 23-380 months]), and 13 HCs (7 males and 6 females, aged: 95.46 ± 86.48 months [range: 13-263 months]) were included. For the absolute band power, the theta power was significantly higher in the high-SUDEP group than in the low-SUDEP group in the central brain region. For the relative band power, the theta power was also significantly higher in the high-SUDEP group than in the low-SUDEP group in the central and occipital brain regions. The alpha power was significantly lower in the high-SUDEP group than in the low-SUDEP group in the central and parietal brain regions. Conclusions: Patients with high SUDEP-7 scores have different EEG features from those with low SUDEP-7 scores, suggesting that EEG may be used as a biomarker of SUDEP in DS. Significance: Early intervention in patients with DS at a high risk of SUDEP can reduce mortality and morbidity. Patients with high theta band powers warrant high-level supervision.